State feedback control for human inspiratory system - Lafta Esmaeel Jumaa Alkurawy; Khalid Gadban Mohammed; Ammar Issa Ismael (International Journal of Electrical and Computer Engineering (IJECE), 2022)
The mathematical modeling of human respiratory system is an essentially part in saving precision information of diagnostic about the disease of cardiovascular respiratory system. The physics of respiratory system and cardiovascular are completely interconnected with each other. In this paper, we will study the state feedback control for the inspiratory system during study the characteristics of the response output with the stability. The model of system is nonlinear and linearized it by Tayler method to be simple to matching with the control theory. We convert the system from differential equation to state equation to find the optimal control that helps to drive the respiratory system. Simulations are managed to indicate the proposed method effectiveness. The results of simulations are validated by using a real information form the health center.